2017
DOI: 10.12659/msm.904546
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Paternal FBN1 Mutation Detected in Embryos Before Implantation

Abstract: BackgroundMarfan syndrome (MFS) is an autosomal dominant disease caused by mutations in the Fibrillin (FBN)1 gene and characterized by disorders in the cardiovascular, skeletal, and visual systems. The diversity of mutations and phenotypic heterogeneity of MFS make prenatal molecular diagnoses difficult. In this study, we used pre-implantation genetic diagnosis (PGD) to identify the pathogenic mutation in a male patient with MFS and to determine whether his offspring would be free of the disease.Material/Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The diagnostic accuracy may be affected when using STR-based haplotype linkage analysis if the recombination occurs between STR loci and target genes. Currently, SNP-based linkage analysis is increasingly applied to PGT-M because SNPs are more widely distributed and exist at higher densities in the genome than STRs ( Wang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnostic accuracy may be affected when using STR-based haplotype linkage analysis if the recombination occurs between STR loci and target genes. Currently, SNP-based linkage analysis is increasingly applied to PGT-M because SNPs are more widely distributed and exist at higher densities in the genome than STRs ( Wang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this approach also has obvious drawbacks. For example, it is difficult to successfully construct a haplotype if the patient has a poor ovarian reserve, with insufficiently mature oocytes ( Wang et al, 2017 ; Chen et al, 2019 ; Yuan et al, 2020 ; Huang et al, 2022 ). The second category uses affected embryos as probands in the linkage phase and analyzes them via NGS.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of MFS relies on family history and multi-system scores. Due to the clinical heterogeneity and diversification of mutations, it is difficult for doctors to diagnose mild cases or prenatal patients 171 . However, with the advancements in genetic testing, this problem is expected to be solved.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, targeted sequencing by NGS was developed, which detected the DNM in FBN1 for PGT-M. However, this required the assistance of a customized probe in the target region and did not detect CNVs and aneuploidy [9]. Moreover, three biopsied blastocysts in this study were considered wild-type homozygotes in the DNM site of FBN1, while the haplotypes were not verified by single-sperm detection and could not exclude ADO in this site which may result in misdiagnoses in the PGT.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, single-nucleotide polymorphism (SNP) array and nextgeneration sequencing (NGS) techniques applied in PGT have enabled more precise diagnosis not only because more genetic markers (such as SNPs) were used instead of the previously used short tandem repeats (STRs), to construct haplotypes, but also because genetic diseases and aneuploidy could be identified concurrently [7,8]. In addition, other studies reported the direct use of genetic information from parent-linked-embryos to phase haplotypes with preliminary target sequencing, but the diagnosis was customized and unavailable for chromosomes [9].…”
Section: Introductionmentioning
confidence: 99%